Combined Carotid Endarterectomy and off Pump Coronary Artery Bypass Grafting: A Case Report - Alam, Saleh Ahmed Nurul; Sharifuzzaman, Mohammad; Chanda, Prosanta Kumar; Rahman, Rafiur; Rahman, Hafizur; Alam, Shafiul; Hossain, Daud (Journal of Bangladesh College of Physicians and Surgeons, 2010)
A 64 years male presented as a case of triple vessel coronary artery disease with bilateral asymptomatic carotid lesion. He underwent combined right carotid endarterectomy (CEA) and off pump coronary artery bypass grafting (OPCAB) with excellent outcome. DOI: 10.3329/jbcps.v27i2.4254 J Bangladesh Coll Phys Surg 2009; 27: 103-106